Fragilities in the U.S. Treasury Market : Lessons from the 'Flash Rally' of October 15, 2014 - Bouveret, Antoine (IMF Working Papers; Working Paper, 2015)
Changes in the structure of the U.S. Treasury market over recent years may have increased risks to financial stability. Traditional market makers have changed their liquidity provision by increasingly switching from risk warehousing to risk distribution, and a new breed of market maker has emerged with the rise of electronic trading. The 'flash rally' of October 15, 2014 provides a clear example of how those risks can materialize. Based on an in-depth analysis of the event-complementing the authorities' work-we suggest i) providing incentives for liquidity provision, ii) improving market safeguards, and iii) enhancing the regulation of the Treasury market.